2007
DOI: 10.1086/512158
|View full text |Cite
|
Sign up to set email alerts
|

Activity and Kinematics of Ultracool Dwarfs, Including an Amazing Flare Observation

Abstract: We present the activity and kinematics of a representative volume-limited (20 pc) sample of 152 late-M and L dwarfs (M7YL8) photometrically selected from the Two Micron All Sky Survey (2MASS). Using new proper-motion measurements and spectrophotometric distance estimates, we calculate tangential velocities. The sample has a mean tangential velocity of hV tan i ¼ 31:5 km s À1 , a velocity dispersion of tan ¼ 20:7 km s À1 , and a maximum tangential velocity of V tan ¼ 138:8 km s À1 . These kinematic results are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

40
224
6
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(272 citation statements)
references
References 77 publications
40
224
6
2
Order By: Relevance
“…In a sample of 152 late-M and L dwarfs, Schmidt et al (2007) found a slightly lower frequency of Hα emitters among the M8 dwarfs and confirmed the decline of Hα emission in L dwarfs. Our data indicates a frequency of Hα emitters that is consistent with that of Schmidt et al (2007) in the range M8-M9, but is significantly lower for the L dwarfs. We do not attach high significance to our results because it is possible that our lower fraction of Hα emitters in the L dwarfs is caused by the low spectral resolution and modest signal-tonoise ratio of our spectra.…”
Section: Chromospheric Activitymentioning
confidence: 59%
See 1 more Smart Citation
“…In a sample of 152 late-M and L dwarfs, Schmidt et al (2007) found a slightly lower frequency of Hα emitters among the M8 dwarfs and confirmed the decline of Hα emission in L dwarfs. Our data indicates a frequency of Hα emitters that is consistent with that of Schmidt et al (2007) in the range M8-M9, but is significantly lower for the L dwarfs. We do not attach high significance to our results because it is possible that our lower fraction of Hα emitters in the L dwarfs is caused by the low spectral resolution and modest signal-tonoise ratio of our spectra.…”
Section: Chromospheric Activitymentioning
confidence: 59%
“…We did not detect any obvious flares in our observations. Schmidt et al (2007) estimated a flare cycle of 5% for late-M dwarfs and of 2% for L dwarfs. Those numbers may need to be revised slightly downwards.…”
Section: Chromospheric Activitymentioning
confidence: 99%
“…Figure 3 shows 8 spectra of previously found M, L and T dwarfs as a comparison. SDSS J1428+5923 was recently confirmed and spectral-typed using its infrared spectrum as an L5 dwarf using the Two Micron Proper Motion (2MUPM) survey, under the name 2MASS J14283132+5923354 (Schmidt et al 2007). SDSS J0249−0034, SDSS J1048+0111, SDSS J1653+6231 and SDSS J1331−0116 were classified by Hawley et al (2002).…”
Section: Red Optical Spectra From the Sdssmentioning
confidence: 99%
“…Other indicators of magnetic activity are most prominently their often strong and variable Hα emission (Gizis et al 2000;Mohanty & Basri 2003;Schmidt et al 2007), suggesting the ubiquity of chromospheres and radio gyrosynchrotron emission, which requires the presence of fast electrons and magnetic fields (Berger 2002). Recently, strong magnetic fields with B f -values of up to a few kG have been detected on several ultracool dwarfs, utilising the profiles of their FeH lines (Reiners & Basri 2007).…”
Section: Introductionmentioning
confidence: 99%